Bulk phase resource ratio alters carbon steel corrosion rates and endogenously produced extracellular electron transfer mediators in a sulfate-reducing biofilm. Issue 6 (3rd July 2019) - Krantz, Gregory P.; Lucas, Kilean; Wunderlich, Erica L.-; Hoang, Linh T.; Avci, Recep; Siuzdak, Gary; Fields, Matthew W.
Abstract: Desulfovibrio alaskensis G20 biofilms were cultivated on 316 steel, 1018 steel, or borosilicate glass under steady-state conditions in electron-acceptor limiting (EAL) and electron-donor limiting (EDL) conditions with lactate and sulfate in a defined medium. Increased corrosion was observed on 1018 steel under EDL conditions compared to 316 steel, and biofilms on 1018 carbon steel under the EDL condition had at least twofold higher corrosion rates compared to the EAL condition. Protecting the 1018 metal coupon from biofilm colonization significantly reduced corrosion, suggesting that the corrosion mechanism was enhanced through attachment between the material and the biofilm. Metabolomic mass spectrometry analyses demonstrated an increase in a flavin-like molecule under the 1018 EDL condition and sulfonates under the 1018 EAL condition. These data indicate the importance of S-cycling under the EAL condition, and that the EDL is associated with increased biocorrosion via indirect extracellular electron transfer mediated by endogenously produced flavin-like molecules.